2013
DOI: 10.1590/s1806-37132013000200002
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between exercise capacity and quality of life in adolescents with asthma

Abstract: OBJECTIVE: To determine whether the quality of life of adolescents with asthma correlates with parameters obtained prior to and after the six-minute step test (6MST); spirometric results after the 6MST; and level of physical activity. METHODS: Nineteen adolescents with asthma, ranging from 11-15 years of age, were assessed with spirometry, 6MST, the International Physical Activity Questionnaire (IPAQ), the Pediatric Asthma Quality of Life Questionnaire (PAQLQ), and the 10-point Borg category-ratio scale. RESUL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 21 publications
2
7
1
4
Order By: Relevance
“…Basso et al . assessed the association between quality of life in adolescents with asthma and parameters in the 6‐min step test, spirometry and physical activity level, and concluded that higher levels of physical activity indicate a better quality of life . In addition, Matsunaga et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Basso et al . assessed the association between quality of life in adolescents with asthma and parameters in the 6‐min step test, spirometry and physical activity level, and concluded that higher levels of physical activity indicate a better quality of life . In addition, Matsunaga et al .…”
Section: Discussionmentioning
confidence: 99%
“…Basso et al assessed the association between quality of life in adolescents with asthma and parameters in the 6-min step test, spirometry and physical activity level, and concluded that higher levels of physical activity indicate a better quality of life. 27 In addition, Matsunaga et al conducted a study with Brazilian asthmatic children and adolescents and concluded that quality of life seems to be directly related to asthma control level. 28 We used IPAQ as the only validated instrument to measure the physical activity level in asthmatic children and adolescents who were not in crisis.…”
Section: Discussionmentioning
confidence: 99%
“…Basso et al performed spirometry and the six-minute step test (6MST) in, as well as administering physical activity and quality of life questionnaires to, 19 adolescents with asthma (11-15 years of age) in Brazil. 30 Those authors concluded that the sensation of dyspnea and leg fatigue reported at the end of the 6MST reflected the discomfort that asthma caused during their activities of daily living.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, those authors demonstrated that asthma causes discomfort in the daily lives of asthma patients, and that this discomfort will consequently result in greater limitation of activities of daily living in patients with poorly controlled asthma and greater asthma severity. 30 , 31 …”
Section: Discussionmentioning
confidence: 99%
“…Uno de los métodos de evaluación más ampliamente empleados para la cuantificación de la tolerancia al ejercicio en pacientes con ERC es el C6M, gracias a su aplicabilidad y validación en diversas enfermedades, así como también, al bajo costo que implica su realización 7,12,13,17 . Sin embargo, son escasos los estudios que han evaluado la asociación entre el deterioro de la función pulmonar y el rendimiento en pruebas de evaluación de la capacidad física en pacientes con BO.…”
Section: Comentariounclassified